Effect of platelet-rich plasma on angiogenic and regenerative properties in patients with critical limb ischemia - Hamid Tanzadehpanah; Sima Nobari; Ava Jalalian Hoseini; Farzaneh Ghotbani; Mohsen Mehrabzadeh; Jamal Jalili shahri; Amirreza Alipour; Mohsen Sheykhhasan; Hamed Manoochehri; Susan Darroudi; Hanie Mahaki (Regenerative Therapy)
Platelet-rich plasma (PRP) is a promising regenerative therapy due to its simplicity, clinical application, safety, and ability to promote angiogenesis. It utilizes various angiogenic growth factors in platelets, including platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF), and epidermal growth factor (EGF), which are integral to the tissue repair.Critical limb ischemia (CLI) is a major symptom of peripheral arterial disease (PAD), and PRP therapy aims to improve blood circulation to the distal limb through the development of blood vessels. This review focuses on the extensive research on the molecular mechanisms of PRPs in treating CLI. A comprehensive search was conducted on Web of Science, PubMed, Google Scholar, and Scopus to find studies published during PRP therapy in critical limb ischemia up to June 2024. Current studies reveal that PRP composition varies by case, affecting preparation methods, storage duration, storage methods, and interaction with other materials. PRP-derived growth factors have shown promising results in treating CLI, but well-controlled human research is scarce despite positive animal studies.